Framing Analysis of Syahrul Yasin Limpo Corruption Case in Online Media - Tamrin, Sopian; Meutia, Fadhillah Sri; Riduan, Imam Malik (JED (Jurnal Etika Demokrasi), 2024)
The corruption case involving Syahrul Yasin Limpo (SYL) became one of the most widely reported events in 2024, reflecting his prominent role as a state official. This study analyzes how online media frame the SYL case and construct public perception using Robert Entman’s framing model—defining problems, diagnosing causes, making moral judgments, and suggesting remedies—alongside Berger and Luckmann’s social construction of reality theory. This study analyzes the framing and construction of reality in ten articles from Detik.com, Kompas.com, Liputan6.com, and CNBC Indonesia were examined. The findings reveal diverse framing approaches: Detik.com emphasizes courtroom drama, Kompas.com maintains neutrality, Liputan6.com highlights SYL’s integrity, and CNBC Indonesia focuses on violations. These differences demonstrate the media’s role in shaping public opinion and monitoring law enforcement. The study recommends that media facilitate critical public discourse to ensure balanced and transparent reporting.